Development of a UPLC-MS/MS method for the determination of orelabrutinib in rat plasma and its application in pharmacokinetics - Liu, Ya-nan; Hu, Yingying; Wang, Jing; Chen, Chaojie; Cai, Jianping; Xu, Ren-ai; Lu, Zhongqiu (Frontiers in Pharmacology, 2022)
The aim of the present study was to establish an ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method for the determination of orelabrutinib in rat plasma using futibatinib as internal standard (IS), where a complete biological analysis method validation was performed, and to apply for a pharmacokinetic study in rats. Orelabrutinib was extracted from plasma by protein precipitation and quantitatively analyzed by UPLC-MS/MS. An Acquity UPLC BEH C18 column was used for rapid separation by gradient elution using 0.1% formic acid and acetonitrile as mobile phases. The validation results of bioanalytical methodology showed that the linearity of orelabrutinib in plasma samples was good within the concentration range of 1-2000 ng/mL, and the lower limit of quantification (LLOQ) was 1 ng/mL. The precision of orelabrutinib ranged from 1.4% to 11.5%, with intra-day and inter-day accuracy ranging from -5.7% to 7.7% and -0.2% to 12.5%, respectively. The selectivity, accuracy, precision, stability, matrix effect and recovery of the method met the requirements of quantitative analysis of biological samples. The method was simple, sensitive, accurate and specific, and had high recovery rate. It also could be successfully applied to the pharmacokinetic study of rats.